NEDD4 Induces K48-Linked Degradative Ubiquitination of Hepatitis B Virus X Protein and Inhibits HBV-Associated HCC Progression - Wan, Tao; Lei, Zhao; Tu, Biao; Wang, Tianyin; Wang, Jiale; Huang, Feizhou (Frontiers in Oncology, 2021)
Neural precursor cell expressed developmentally downregulated gene 4 (NEDD4) plays two opposite roles in carcinogenesis. It has been reported that NEDD4 inhibits hepatocellular carcinoma (HCC) progression; however, little is known about its potential function and molecular mechanism in HCC in the context of hepatitis B virus (HBV) infection. In this study, we analyzed NEDD4 expression in 199 HCC specimens with or without HBV infection and observed that NEDD4 expression was unrelated to HBV exposure in HCC tumor tissue but that high NEDD4 expression conferred better overall survival (OS) and progression-free survival (PFS) than low NEDD4 expression in patients with HBV-associated HCC. Upregulation of NEDD4 inhibited proliferation, migration and invasion in HBV-related HCC cell lines. We demonstrated that NEDD4 interacts with HBV X protein (HBx) and that HBx upregulation could reverse the suppression of proliferation and mobility induced by NEDD4 overexpression. Furthermore, we confirmed that NEDD4 induced the degradation of HBx in a ubiquitin/proteasome-dependent manner via K48-linked ubiquitination. Our findings suggest that NEDD4 exerts a tumor-suppressive effect in HBV-associated HCC by acting as an E3 ubiquitin ligase for HBx degradation and provide new insights into the function of NEDD4.